PENGARUH INSENTIF FINANSIAL DAN INSENTIF NON FINANSIAL TERHADAP KEPUASAN KERJA PENGEMUDI MITRA GOJEK KOMUNITAS LASKAR SASAJI BANDUNG AREA CILIWUNG PT KARYA ANAK BANGSA - Nugroho, Muchamad Fuad Hardi (Journal Competency of Business, 2021)
This study aims to determine how the influence of financial incentives and non-financial incentives on job satisfaction of Gojek partner drivers, Laskar Sasaji community, Bandung, Ciliwung area. This research is quantitative. The population of this study is Gojek's partners, the Laskar Sasaji community in Bandung, the Ciliwung area, which was taken as a sample of 40 people. The data analysis technique used multiple linear regression analysis, t test and F test. The results of the study simultaneously showed that there was a positive influence of financial incentives and non-financial incentives on job satisfaction of Gojek partners, Laskar Sasaji community, Bandung, Ciliwung area. Partially financial incentives have a significant effect and partially non-financial incentives have no significant effect.